Analisis Beban Kerja Karyawan Pada CV. Petroasia Jaya Utama - Syafira Alaina; Uus Mohammad Darul Fadli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Employees are important in the company, they must be guaranteed and maintained by the company. This relates to paying attention to workload on employees. The purpose of this study was to determine and analyze the workload on employees of CV. Petroasia Jaya Utama. This article identifies 2 dimensions of workload, namely internal factors and external factors. This research uses a qualitative descriptive method, this research also involves interviews and observations. The interviewees in this study involved 5 employees at the research location at CV. Petroasia Jaya Utama. The results showed that internal and external workloads have a significant influence on employee performance. Employees who experience excessive workload and an uncomfortable work environment tend to experience fatigue and are less productive. Therefore, companies should pay attention to employee workload and take steps to reduce workload and improve the quality of the work environment. The results of this study can be used as reference material for companies to improve employee performance and reduce the workload faced by employees.